PENGARUH PELATIHAN TERHADAP KINERJA KARYAWAN PADA ROOM DIVISION DI ANGKASA GARDEN HOTEL PEKANBARU - Mulyadi, Mulyadi (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This study aims to determine the effect of training on employee performance room division Angkasa Garden Hotel Pekanbaru. Using a total sample of 31 people. In this study the authors used quantitative descriptive research method by using the SPSS17 method. From the result of the research, the number of training variables is 5,647 and the value of ttabe ladalah 2.045.sehinggathitung (5.647) >ttabel (2.045) and the significant value 0.000 < 0.05, so it can be concluded that the training variables positively affect the performance variable. In the determination coefficient test (R2) in the value of R = 0.524 means the relationship of free variables (training) to variable terikan (performance) of 52.4% while the remaining 47.6% influenced by other variables that are not examined. Finally from this research can be concluded that the training has a positive and significant impact on the performance, so it is suggested to Angkasa Garden Hotel Pekanbaru in order to maintain and improve the training of employees room division in particular and all employees in general to produce maximum performance